(3GdfXGe GdbGfhfi dfRY GdedcjI ai GdJTQjY GdCQOfi (B: s (3OQGSI ebGQfI (B/ s - (3fTCJ eMeO YHOGdbGOQ Hfi MeOs; (3QCaJ EHQGgje ahOIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3Cf fRY GdedcjI ddefaYI GdYGeI eYJQa Hg bOjekG h MOjKkG(B: (3h Cfg JUQa ef JUQaGJ GdSdWI GdYGeI (B((3Ci GdOhdI(B) (3h gh eG COi Edi GdGYJQGa ddOhdI hMOgG HeeGQSI gPG GdMb habkG ddTQhW GdeMOOI bGfhfkG dCedGc GdZjQ(B: (3h dG jKjQ Cj ETcGd HTCf JMOjO GdZjQ MjK Ef fRY GdedcjI jfUH Ydi CehGd GdNhGU CjkG cGf hVYge GdbGfhfj h GdPjf dge UdI bGfhfjI HGdeGd GdefRhY(B. (3ZjQ Cfg EPG cGfJ GdOhdI hMOgG gj UGMHI GdMb aj EUOGQ GdJUQaGJ GdbGfhfjI GdeGSI HedcjGJ GdCaQGO aj EWGQ fRY GdedcjI ddefaYI GdYGeI(B: (3aEf GdJSGDd GdeWQhM aj gPG GdeLGd(B. (3ef dg GdMb aj YedjI fRY GdedcjI ddefaYI GdYGeI? Ci JMOjO GdLgGJ GdMchejI GdeSJajOI ef YedjI fRY GdedcjI ddefaYI GdYGeI(B: (3h cPdc eGgjI GdCehGd GdLGFR fRY edcjJgG ddefaYI GdYGeI? dGSjeG h Cf GdCehGd HTcdkG YGe JfbSe Edi CehGd efbhdI h CehGd ZjQ efbhdI (B((3YbGQGJ(B). (3h cPdc ef ge GdCTNGU GdeJVQQjf ef YedjI fRY GdedcjI ddefaYI GdYGeI? Ef Mb GdedcjI Mb ebOS jMQe GdeSGS Hg(B: (3h bO YQa GdeTQY GdCQOfj Mb GdedcjI aj GdeGOI (B(1018) (3ef GdbGfhf GdeOfj GdCQOfj Qbe (B(43) (3dSfI (B1976(3HCfg(B: (3Mb GdedcjI gh SdW``I GdeGd``c a`j Cf jJUQa a`j edc``g JUQakG eWd`b`kG YjfkG h efaYI h GSJZdGdkG(B. (3hdeGdc GdTjA hMOg Cf jfJaY HGdYjf GdeedhcI h HZdJgG h KeGQgG h fJGLgG h jJUQa aj YjfgG HLejY GdJUQaGJ GdLGFRI TQYkGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2018s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B484-504s
Keywords: (3GdbGfhf GdYGes; (3GdCedGcs; (3GdefaYI GdYGeIs; (3GdbQGQGJ GdEOGQjI GdZjQ eTQhYIs; (3GdeUGOQIs; (3GdGSJjdGA GdeDbJs; (3GdbGfhf GdCQOfjs; (3OYhj GdEdZGAs; (3GdCQcGf GdehVhYjIs; (3ELQGAGJ fRY GdedcjIs; (3YOe GdCNJUGU s; (3GdJYhjVs; (3GdbGVj GdEOGQjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes